1971
DOI: 10.1530/jrf.0.0240449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Age on Postimplantation Reproductive Failure in Mice

Abstract: Summary. Postimplantation reproductive failure was studied in young adult, 9-, 11-, 13-and 15-month-old C57BL/6J mice. Loss of all implanted embryos between the 8th and 18th days of pregnancy increased with advancing maternal age. The percentage of individual postimplantation deaths increased from 9% in young adults to 23% in 9-month-old mice and further increased to 45% in 11-month-old animals. Evidence is presented that deaths most commonly occurred in the early postimplantation period. Harman & Talbert (197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Our findings that the decline in reproductive capacity was not primarily due to a reduction in ovulation rate agrees with reports in the hamster (Thorneycroft & Soderwall, 1969) and in some rodents (Talbert, 1968). Aged does at 12 and 24 days post coitum had 71-3% and 76-7% as many CL, 48-4% and 45-6% as many implantation sites and only 14-0% and 20-0% as many viable embryos, respectively, as did the young does ( Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings that the decline in reproductive capacity was not primarily due to a reduction in ovulation rate agrees with reports in the hamster (Thorneycroft & Soderwall, 1969) and in some rodents (Talbert, 1968). Aged does at 12 and 24 days post coitum had 71-3% and 76-7% as many CL, 48-4% and 45-6% as many implantation sites and only 14-0% and 20-0% as many viable embryos, respectively, as did the young does ( Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…A reduction in the number of total follicles and an increase in atretic follicles with increasing age has been noted in several species (Talbert, 1968). The larger number of follicles in young rabbits, particularly towards the end of the gestation period, has previously been reported (Adams, 1968) and may be important in maintaining CL function through oestrogen production (Keyes & Nalbandov, 1967 (1970) reported that prenatal loss in rabbits mainly occurred after Day 10.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Progesterone was found to have a significant effect but the oestrogen effect was not significant. (Harman & Talbert, 1970), although such changes could be a result of pregnancy loss (Talbert, 1971), and the histological assessment of luteal function is not reliable (Finn, 1970 (Finn, 1963) or by giving orthotopic ovarian grafts from young mice (Krohn, 1966). Measurements of plasma progestins in the hamster (Blaha, 1971) and in the rabbit (Spilman, Larson, Concannon & Foote, 1972) have shown that hormone levels are similar in young and old animals, except when there were no viable fetuses late in pregnancy (Spilman et al, 1972), and supplementary progesterone and oestrogen did not increase embryonic survival in old rabbits (Larson, Spilman, Dunn & Foote, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…These mice were then housed at the Central Animal Facility at the Otto-vonGuericke University Magdeburg, Medical Faculty, with a 12 h light:12 h darkness cycle. In all experiments, mice at the age of 10-16 weeks were used to avoid age-dependent influences on their reproductive phenotype (Talbert 1971, Parkening et al 1978, Holinka et al 1979. All procedures were in accordance with the institutional guidelines of Magdeburg, and the study was previously approved by the Landesdirektion Dessau (42502-2-978 Magdeburg).…”
Section: Animalsmentioning
confidence: 99%